Poeci i Róża: wiersze polskich poetów w tłumaczeniu Rozy Alimpijewej jako ilustracja koncepcji przekładu wo/man - Borys, Iwona (Acta Polono-Ruthenica, 2018)
Rosa Alimpieva, professor of Immanuel Kant Baltic Federal University in Kaliningrad, is known in Poland as a linguist, specialist in history of the Russian language and TS, but also as a great popularize of a Polish poetry and culture in Russia, especially in Kaliningrad Oblast. She translated into Polish from Russian selectes masterpieces of Polish poetry: poems of Adam Mickiewicz, Juliusz Słowacki, Adam Asnyk, Leopold Staff, Konstanty Ildefons Gałczyński, Czesław Miłosz, Jarosław Iwaszkiewicz. She decided also to translate into Russian some poems of her Polish friends Walenty Piłat and Krzysztof Dariusz Szatrawski. The translation has been acknow- ledged by Polish writers as very accurate and , but we think that the world of Polish poets (especially Mickiewicz) in Alimpieva’s translation is especially close to perception competence of the Russian reader.